Literary Jacobitism - Pickard, C; Pickard, Claire (2006)
﻿ This thesis argues that much of the gender based criticism that has led to the "rediscovery" of neglected early modern women writers has, paradoxically, also served to limit our understanding of such writers by distracting attention from other aspects of their writing, such as their political commitments. The three authors considered, Jane Barker (1652-1732), Mary Caesar (1677-1741) and Anne Finch (1661-1720), have been selected precisely because Jacobitism is central to their writing. However, it will be argued that a focus upon gender politics in the texts of these writers has led to a failure to comprehend the party political boldness of their work. The thesis examines the writing of each author in turn and explores the implications of Barker's, Caesar's and Finch's Jacobite allegiances for their respective views of human history as played out in political affairs. It also considers the ways in which each author attempts to reconcile a cause that is supposedly supported by God with apparent political failure. The quest of Barker, Caesar and Finch to investigate these issues and to comprehend how Jacobitism forms part of their own authorial identities is central to what is meant here by "literary Jacobitism" in relation to these writers. The thesis demonstrates that Jacobitism is enabling for each of these three women as it enhances their ability to conceive of themselves as authors by allowing their sense of political identity to overcome their scruples about their position as women who write. However, it also illustrates that Jacobitism functions differently in the writing of each of the selected authors. It thus argues that an undifferentiated labelling of the work of these three women as "Jacobite" is as restrictive as their previous categorisation as "women writers".